Hydraulic tiles and memory: Theoretical bases to support the construction of a graphic inventory - Aguiar Mol, Iara; Silva, Sérgio Antônio (Base Diseño e Innovación, 2019)
The present article proposes to elaborate a literature review on the theme of memory, with the purpose of providing theoretical basis to guide the construction of a graphic collection of patterns of hydraulic tiles in Brazil. The subject is part of a more comprehensive research that intends to identify and discuss issues pertinent to the relevance of hydraulic tile patterns, as artifacts of memory, identity and Brazilian material culture. Based on initial concepts about memory, we will try to understand the implications of this term for the registration of cultural heritage, besides raising and registering some methods and taxonomies that can be applied in the cataloging of collections and inventories of such nature. In other words, it is sought to find the best way to organize this visual repertoire so that it can enable to gather a cultural patrimony appropriate to the activation of individual and collective memories and, at the same time, to extend creative potentialities in contemporary design processes, making graphic forms.